SCREENING FOR ANTIBIOTIC PRODUCING MARINE BACTERIA AGAINST FISH PATHOGENS - PREM ANAND, T.; C. CHELLARAM; S. KUMARAN; C. FELICIA SHANTHINI (International Journal of Pharma and Bio Sciences, 2011)
The need for the development of new antibiotics to counter drug resistance in bacterial pathogens has been stressed by various researchers worldwide. As the discovery of novel chemical classes have been in decline for the past two decades, the need to exploit new resources in search for effective chemicals with novel mechanism of actions is imperative. Marine bacteria are such a resource yet to be tapped, and the potential it offers is vast. Aquaculture has developed into a prime industry to tap the enormous turnover of bio-energy for the benefit of mankind. Since aquaculture depends on self-renewable natural resources, it has infinite future for hundreds of years to come. Aquaculture is also being viewed as the only alternative to augment fish production due to over exploitation of natural fish resources. In this present study a total of 633 marine bacterial strains were isolated. In the initial antibiotic production test using E.coli, 170 strains were found to be antibiotic producers and out of which 101 strains were found to be active against 3 major fish pathogens namely Vibrio harveyi, V. parahaemolyticus, Aeromonas hydrophilla. In the genus level identification of the potential strains the genus Alteromonas sp. dominated followed by Streptomyces sp., Vibrio sp., Bacillus sp., Flavobacterium sp. and Pseudomonas sp